2012
DOI: 10.1186/2190-4715-24-23
|View full text |Cite
|
Sign up to set email alerts
|

Surveying the occurrence of subspontaneous glyphosate-tolerant genetically engineered Brassica napus L. (Brassicaceae) along Swiss railways

Abstract: Background: Railway tracks represent a highly interlinked habitat with numerous possibilities for accidental entry of oilseed rape due to seed spill during transportation. Moreover, glyphosate is regularly employed to control the vegetation, increasing the possibility of establishment for plants resistant to it. We surveyed the presence of genetically engineered glyphosate tolerant oilseed rape (Brassica napus) with a focus on the most important Swiss railway stations. Our objective was to detect accidental es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…This moratorium will last at least until the end of 2017 (FASC 2003), and the control and monitoring of feral GM plants is mandatory (FASC 2008). Nevertheless, feral GM OSR has been found repeatedly in Switzerland (Hecht et al 2014;Schoenenberger and D'Andrea 2012;Schulze et al 2014). In the most recent study, the occurrence of feral herbicide resistant GM OSR events GT73 (Roundup Ready, Monsanto), MS8×RF3, MS8 and RF3 (all traded as InVigor, Bayer CropScience) has been reported for the Rhine port of Basel in Switzerland ).…”
Section: Introductionmentioning
confidence: 92%
“…This moratorium will last at least until the end of 2017 (FASC 2003), and the control and monitoring of feral GM plants is mandatory (FASC 2008). Nevertheless, feral GM OSR has been found repeatedly in Switzerland (Hecht et al 2014;Schoenenberger and D'Andrea 2012;Schulze et al 2014). In the most recent study, the occurrence of feral herbicide resistant GM OSR events GT73 (Roundup Ready, Monsanto), MS8×RF3, MS8 and RF3 (all traded as InVigor, Bayer CropScience) has been reported for the Rhine port of Basel in Switzerland ).…”
Section: Introductionmentioning
confidence: 92%
“…From existing data, it can be concluded that maize (Zea mays) in Mexico [3,4,[38][39][40][41] and oilseed rape (B. napus) in the USA [42], Australia [43,44] and Europe [45][46][47] are likely to have escaped regulatory control, but it is unclear to which extent gene flow to wild relatives has already occurred. Finally, in the cases of rice (Oryza sativa) in China [48,49], black poplar (Populus nigra) in China [50][51][52] and papaya (Carica papaya) in Thailand [53], it can be expected that transgenes will introgress natural populations, though evidence is not yet available.…”
Section: Survey Of Other Related Cases Of Gene Flowmentioning
confidence: 99%
“…Conventional and GM oilseed rape can establish feral (spontaneous or subspontaneous) populations on various types of non-cropped land (Pessel et al 2001, Yoshimura et al 2006, Elling 2008, Elling et al 2009, Kawata et al 2009, Nishizawa et al 2009, Schafer et al 2011, Schoenenberger and D'Andrea 2012. These populations occur frequently along transportation routes (e.g.…”
Section: Oilseed Rape As An Example Of Spread Persistence and Outcromentioning
confidence: 99%